2011
DOI: 10.1007/s10499-011-9490-4
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of differential utilization of plant-based diets by rainbow trout

Abstract: Microarray analysis was conducted using liver samples from two families of rainbow trout that differed in their growth responses when compared between individuals fed a fishmeal or plant protein-based diet. Differential expression relating to dietary utilization between the two families found significant changes in expression of 33 expressed sequence tags (ESTs). Eight of the differentially expressed ESTs had identified mammalian homologs that had been previously researched with identified cellular interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…The transcriptomic analysis also revealed a genetic variability in the expression of genes involved in different immunity pathways, linked to their capacity to grow with a diet devoid of FO and FM. Previous studies found similar results in sea bass and RBT (Geay et al, 2011 ; Overturf et al, 2012 ). Although no differences in immune parameters were detected among lines, analyses of gene expression may be more sensitive with respect to detecting differences among the fish.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The transcriptomic analysis also revealed a genetic variability in the expression of genes involved in different immunity pathways, linked to their capacity to grow with a diet devoid of FO and FM. Previous studies found similar results in sea bass and RBT (Geay et al, 2011 ; Overturf et al, 2012 ). Although no differences in immune parameters were detected among lines, analyses of gene expression may be more sensitive with respect to detecting differences among the fish.…”
Section: Discussionsupporting
confidence: 77%
“…One of the potential ways to further reduce the use of fish oil and fishmeal is to thus take advantage of the genetic variability which exists in the salmonid population. With this objective, we sought to identify the mechanisms implemented by some trout genotypes to grow more efficiently with a complete plant-based diet, as until now, this question has been little studied (Geay et al, 2011 ; Overturf et al, 2012 ; Callet et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of plant-based diets have been largely studied, but only few transcriptomic studies have analysed the effect of fish genetic background. Overall, these studies indicated only a limited number of genes to be differentially expressed according to the genotype in RBT [ 20 , 21 ], in salmon [ 11 ] or in sea bass [ 14 ]. In the present experiment, we found a high number of genes differentially expressed between genotypes, with a cut-off p-value corrected for multiple testing, controlling thus the number of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…A study on European sea bass revealed differences between two families characterized by their different abilities to use a plant-based diet [ 14 ]. And only two studies focused on RBT, and analysed two families with different ability to grow with a diet devoid of fishmeal [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%